2015
DOI: 10.1159/000431387
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome Painting in <b><i>Vanellus chilensis</i></b>: Detection of a Fusion Common to Clade Charadrii (Charadriiformes)

Abstract: The Southern lapwing (Vanellus chilensis) is endemic to America and is well-known because of the vast expansion of its geographical distribution and its involvement in air accidents. Despite its popularity, there is no information concerning the genomic organization and karyotype of this species. Hence, because other species of the genus Vanellus have variable diploid numbers from 2n = 58 to 76, the aim of this report was to analyze the karyotype of V. chilensis by means of classical and molecular cytogenetics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
33
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(40 citation statements)
references
References 17 publications
6
33
1
Order By: Relevance
“…Some species of Gruiformes and Charadriiformes, which form a clade with Opisthocomiformes according to whole-genome analysis [Jarvis et al, 2014;Cracraft et al, 2015], have been analyzed by chromosome painting. These studies revealed the presence of a few chromosome synapomorphies which reinforced the monophyly of each order [Nanda et al, 2011;Furo et al, 2015b;Kretschmer et al, 2015b]. For instance, the fission of the syntenic group corresponding to GGA5q represented a synapomorphy for Gruiformes species.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Some species of Gruiformes and Charadriiformes, which form a clade with Opisthocomiformes according to whole-genome analysis [Jarvis et al, 2014;Cracraft et al, 2015], have been analyzed by chromosome painting. These studies revealed the presence of a few chromosome synapomorphies which reinforced the monophyly of each order [Nanda et al, 2011;Furo et al, 2015b;Kretschmer et al, 2015b]. For instance, the fission of the syntenic group corresponding to GGA5q represented a synapomorphy for Gruiformes species.…”
Section: Discussionmentioning
confidence: 80%
“…For instance, the fission of the syntenic group corresponding to GGA5q represented a synapomorphy for Gruiformes species. The fusion between syntenic groups corresponding to GGA7 and GGA8 was found in the only 2 species of Charadriiformes analyzed by FISH, despite the huge difference in their diploid numbers (2n = 42 in B. oedicnemus and 2n = 82 in Vanellus chilensis ), and might represent a chromosome signature for the clade Charadrii [Nie et al, 2009;Kretschmer et al, 2015b]. However, none of these rearrangements were found in the hoatzin.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…BOE5 was divided into two pairs, AMA7 and AMA8, but this was not by ssion. Cytogenetic studies demonstrated that the fusion of PAK7 and PAK8 is a characteristic of suborder Charadrii [21]; the presence of the separate chromosomal pairs in Actitis is the ancestral form, and BOE5 is the derived form (Fig. 4E).…”
Section: Discussionmentioning
confidence: 99%
“…2) Larus argentatus (LAR, 2n = 70) was hybridized with BOE probes, which demonstrated several associations (e.g., BOE6 / BOE10 and BOE7 / BOE9) that were proposed as signatures for suborder Lari [20]. 3) Vanellus chilensis (VCH, 2n = 78) was hybridized with GGA probes; this demonstrated the fusion of GGA 7 and GGA 8, which was proposed as a possible common characteristic in suborder Charadrii [21]. 4) Jacana jacana (JJA, 2n = 82), which was also hybridized with GGA probes and presented numerous ssions and fusions, demonstrating that JJA had undergone extensive genomic reorganization [8].…”
Section: Introductionmentioning
confidence: 99%